2018
DOI: 10.1007/s13205-018-1142-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanozeolite and plant growth promoting rhizobacteria on maize

Abstract: Plant growth promoting rhizobacteria are key to soil and plant health maintenance. In the present study, two PGPR strains which were identified as spp. (accession number KX650178 and KX650179) with nanozeolite (50 ppm) were applied to the seeds in different combinations and tested on growth profile of maize crop. Various growth related parameters, including plant height, leaf area, number of leaves chlorophyll and total protein were positively increased up to twofold by the nanocompound treatment. GC-MS result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…Increased plant and root length, leaf number and area were also observed in treated plants over control. Similarly, Khati et al [ 36 , 37 ] reported improved seed germination, plant and root length, leaf area, chlorophyll and carotenoid content in maize plant under the treatment of nanozeolite and nanochitosan. Application of nanochitosan enhanced the growth of Pantoea agglomerans and Pseudomonas taiwanensis [ 38 ] .…”
Section: Discussionmentioning
confidence: 96%
“…Increased plant and root length, leaf number and area were also observed in treated plants over control. Similarly, Khati et al [ 36 , 37 ] reported improved seed germination, plant and root length, leaf area, chlorophyll and carotenoid content in maize plant under the treatment of nanozeolite and nanochitosan. Application of nanochitosan enhanced the growth of Pantoea agglomerans and Pseudomonas taiwanensis [ 38 ] .…”
Section: Discussionmentioning
confidence: 96%
“…Application of Bacillus spp. improved maize growth and soil fertility by improving the nutrient status of the soil [59][60][61]. PSB increased the urease and dehydrogenase activity [62].…”
Section: Discussionmentioning
confidence: 99%
“…PR14 in rice and millets [ 13 ], whilst two Bacillus spp. strains mixed with nanozeolite were applied to the seeds on maize crop [ 47 ] and other.…”
Section: Introductionmentioning
confidence: 99%